2017
DOI: 10.1007/s40096-017-0225-1
|View full text |Cite
|
Sign up to set email alerts
|

Homotopy analysis for the influence of Navier slip flow in a vertical channel with cross diffusion effects

Abstract: This research is to examine the laminar, incompressible free convective Navier slip flow between vertical plates with cross diffusion effects. This investigation includes the first order chemical reaction also. The resulting equations with boundary conditions are reduced into dimensionless form using suitable transformations. Homotopy analysis method has been applied to solve the system. The influence of emerging parameters on fluid flow quantities have been presented graphically. In addition, the nature of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this article, the free convection flow in an annulus with Navier slip condition [17][18][19] and convective boundary condition [20][21][22][23] has been studied along with cross diffusions and first order chemical reaction. Homotopy analysis method (HAM) [24][25][26][27][28] has been applied to get the solution of the present system. The survey clearly showed that the combined effects with slip flow condition and the convective boundary with cross diffusion in an annulus region have not been reported by any researcher.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, the free convection flow in an annulus with Navier slip condition [17][18][19] and convective boundary condition [20][21][22][23] has been studied along with cross diffusions and first order chemical reaction. Homotopy analysis method (HAM) [24][25][26][27][28] has been applied to get the solution of the present system. The survey clearly showed that the combined effects with slip flow condition and the convective boundary with cross diffusion in an annulus region have not been reported by any researcher.…”
Section: Introductionmentioning
confidence: 99%
“…The h curve of φ(λ) The zero-order deformations; N 1 , N 2 and N 3 are non-linear operators; the average residual errors of f, θ and φ are considered as explained in the work of Kaladhar and Komuraiah [27]. h-curves are plotted with Re = 2, P r = 0.71, Sc = 0.22, Br = 0.5, Gr T = 4, Gr C = 4, Sr = 0.5, D f = 0.5, K = 0.5, α = 0.1, Bi = 0.5, b = 1 for the optimal values of h 1 , h 2 and h 3 and are shown in Figs 2-4.The admissible values of h 1 , h 2 and h 3 are evaluated as -0.34, -0.38, -1.34 respectively with the average residue errors (as explained in[27]) shown if Figs. 5-7.…”
mentioning
confidence: 99%
“…They employed Runge-Kutta fourth order numerical technique to obtain the computational results for nonlinear ordinary differential equations. Kaladhar and Komuraiah [31] employed Homotopy analysis method to investigate the influence of Navier slip flow in a vertical channel with cross diffusion effects. In most of the above-mentioned investigations, the entropy generation is relaxed which is one of the objectives of this study.…”
Section: Introductionmentioning
confidence: 99%